Labor Market Distortions in Cote d'Ivoire : Analyses of Employer-Employee Data from the Manufacturing Sector - Kristensen, Nicolai (2012)
This paper investigates the extent and nature of distortions in the labor market in the Republic of Cote d'Ivoire by using quantile regression analysis on employer-employee data from the manufacturing sector. We found that the labor markets in Cote d'Ivoire do not seem to be much distorted. Unions may influence employment through tenure but do not seem to influence wages directly except for vulnerable minorities that seem protected by unions. Establishment-size wage effects are pronounced and highest for white-collar workers. This may be explained by the efficiency wage theory, so that, even in the absence of unions, segmentation and inefficiencies will still be present as long as firms seek to retain their employees by paying wages above the market clearing level. The inefficiency arising from establishment-size wage effects can be mitigated by education. Furthermore, the premium to education is found highly significantly positive only for higher education, and not for basic education, indicating that educational policies should also focus on higher education.